Survival analysis of osteosarcoma patients: A 15-year experience - Yasin, Nor Faissal; Abdul Rashid, Muhammad Lutfi; Singh, Vivek Ajit (SAGE Publications (UK and US), 2020)
Introduction: Management of osteosarcoma has evolved considerably for the past two decades and there have been changes of practices especially pertaining to chemotherapy regime. This is a review of our cases in the past 15 years. Method: This is a retrospective survival analysis study of 128 patients treated at University Malaya Medical Centre (UMMC) from 1997 to 2011. Results: There were 80 (62.5%) male and 48 (37.5%) female patients with the median age being 15 (5–59). Majority had osteosarcoma of extremities (94.5%). More than 60% patients developed metastasis throughout the course of treatment with 39% presenting with lung metastasis. Osteoblastic osteosarcoma was the commonest subtype (65.6%). Of the 109 patients treated surgically, 84 patients (65.6%) underwent limb salvage surgery while the rest underwent amputation. Seventy-one per cent of patients completed treatment with local recurrence rate of 22.7%. The 5-year and 10-year survival rates were 56.31% (95% CI: 46.20, 65.24) and 22.33% (95% CI: 14.86, 30.76), respectively. The 5-year event-free survival was 52.94% (95% CI: 41.83, 62.87). In multivariate analysis, the independent prognostic factors were presence of metastasis and completion of treatment for both 5-year and 10-year overall survival. Good histological response was only significant for multivariate analysis at 5 years. Patients with metastasis had a hazard ratio of 20.4 at 5 years and 3.26 at 10 years. Conclusion: Overall survival rate for osteosarcoma patients at our centre was comparably higher than other centres in the region. Two independent risk factors for survival are metastatic status and completion of treatment. A standardized chemotherapy regime is essential for long-term survival. © The Author(s) 2020.